1990
DOI: 10.1037/0022-3514.58.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles and fear of personal death: A case study of affect regulation.

Abstract: The relation between attachment styles and fear of personal death was assessed. We classified a sample of Israeli undergraduate students into secure, ambivalent, and avoidant attachment groups and assessed the extent of, and the meaning attached to, overt fear of personal death as well as the extent of fear at a low level of awareness. Ambivalent subjects exhibited stronger overt fear of death than did secure and avoidant subjects, and both ambivalent and avoidant subjects showed stronger fear of death at a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
289
1
18

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(334 citation statements)
references
References 33 publications
26
289
1
18
Order By: Relevance
“…For example, researchers have examined the influence of working models on the inferences people make about their partner's intentions (Collins, 1996); the interplay of distress and working models as determinants of attachment and caregiving behavior Simpson, Rholes, & Nelligan, 1992); the role of working models in partner preferences (Chappell & Davis, 1998;Frazier, Byer, Fischer, Wright, & DeBord, 1996;Pietromonaco & Carnelley, 1994), relationship stability Kirkpatrick & Hazan, 1994), and relationship dissolution (Feeney & Noller, 1992;Pistole, 1995;Simpson, 1990); and the psychodynamic organization and functioning of working models (Bartholomew, 1990;Fraley, Davis, & Shaver, 1998;Fraley & Shaver, 1997;Mikulincer, 1998;Mikulincer, Florian, & Tolmacz, 1990;Mikulincer & Orbach, 1995).…”
Section: Strengths Of An Attachment-theoretical Approachmentioning
confidence: 99%
“…For example, researchers have examined the influence of working models on the inferences people make about their partner's intentions (Collins, 1996); the interplay of distress and working models as determinants of attachment and caregiving behavior Simpson, Rholes, & Nelligan, 1992); the role of working models in partner preferences (Chappell & Davis, 1998;Frazier, Byer, Fischer, Wright, & DeBord, 1996;Pietromonaco & Carnelley, 1994), relationship stability Kirkpatrick & Hazan, 1994), and relationship dissolution (Feeney & Noller, 1992;Pistole, 1995;Simpson, 1990); and the psychodynamic organization and functioning of working models (Bartholomew, 1990;Fraley, Davis, & Shaver, 1998;Fraley & Shaver, 1997;Mikulincer, 1998;Mikulincer, Florian, & Tolmacz, 1990;Mikulincer & Orbach, 1995).…”
Section: Strengths Of An Attachment-theoretical Approachmentioning
confidence: 99%
“…This 15-item scale was found to be highly reliable and valid in studies of Israeli samples. [32][33][34] Similar to Birnbaum et al 34 items corresponding to each style were averaged, the values of these scores were compared and each participant was assigned to the style that had …”
Section: Attachment Styles Questionnaire (As)mentioning
confidence: 99%
“…This questionnaire, developed by Mikulincer et al 32 is based on the descriptions of Hazan and Shaver 14 of feelings and cognitions regarding attachment, each corresponding to an attachment style, and was used to define the personal attachment style of each respondent (secure, ambivalent or avoidant). The AS questionnaire consists of 15 statements (5 statements per attachment style), eg 'I find it relatively easy to get close to others' (secure attachment), 'I am somewhat uncomfortable being close to others' (avoidant attachment), and 'I find that others are reluctant to get as close as I would like' (ambivalent attachment style).…”
Section: Attachment Styles Questionnaire (As)mentioning
confidence: 99%
“…Although no research has tracked attachment styles longitudinally from early childhood to adulthood, cross-sectional studies have found proportions of adult attachment prototypes roughly equivalent to those found in infancy (e.g., Hazan & Shaver, 1987;Mikulincer, Florian, & Tolmatz, 1990;Mikulincer, Florian, & Wellet;Mikulincer & Nachshon, 1991 ), a pattern of results consistent with the notion of continuity (Rothbard & Shavea;. In contrast to the continuity view, other investigators argue that extant measures of adult attachment, particularly self-report instruments, may be heavily influenced by current relationship functioning (Bartholomew, 1994;Kobak, 1994).…”
mentioning
confidence: 99%